A Population-Based Exploration of the Social Implications Associated with Cleft Lip and/or Palate. Issue 6 (June 2017) - Glener, Adam D.; Allori, Alexander C.; Shammas, Ronnie L.; Carlson, Anna R.; Pien, Irene J.; Aylsworth, Arthur S.; Meyer, Robert; Pimenta, Luiz; Strauss, Ronald; Watkins, Stephanie; Marcus, Jeffrey R.
Abstract : Background: Clefts of the lip and/or palate (CL/P) carry a social stigma that often causes psychosocial stress. The purpose of this study was to consider the association of cleft phenotype and age with self-reported aspects of psychosocial stress. Methods: Children with nonsyndromic CL/P and unaffected children born between 1997 and 2003 were identified through the North Carolina Birth Defects Monitoring Program and North Carolina birth records, respectively. The psychosocial concerns of children with CL/P were assessed via a 29-question subset of a larger survey. Responses were analyzed according to school age and cleft phenotype (cleft lip with/without cleft alveolus, CL ± A; cleft palate only, CP; or cleft lip with cleft palate, CL + P). Results: Surveys were returned for 176 children with CL/P and 333 unaffected children. When compared with unaffected children, responses differed for CL ± A in 4/29 questions, for CP in 7/29 questions, and for CL + P in 8/29 questions ( P < 0.05). When stratified by school age, children with CL/P in elementary, middle, and high school differed from unaffected children by 1/29, 7/29, and 2/29 questions, respectively. Middle school–aged children with CL/P were more affected by aesthetic concerns, bullying, and difficulties with friendship, and social interaction. Children with CL + P reported more severe aesthetic-related concerns than children with CL ± A or CP but experienced similar speech-related distress as children with CP only. Conclusion: Social implications associated with CL/P are most pronounced during middle school, and less so during elementary and high school. This information identifies areas of social improvement aimed at reducing the stigma of CL/P.